Periodic Structures : Mode-Matching Approach and Applications in Electromagnetic Engineering. - Hwang, Ruey-Bing (Raybeam) (Wiley, 2012)
Provides readers an understanding of the basic physics underlying meta-materials, providing a powerful tool for analyzing their electromagnetic properties Periodic Structures: Mode-Matching Approach and Applications in Electromagnetic Engineering presents the scattering and guiding characteristics of periodic structures using the mode-matching approach and their applications in electromagnetic engineering. The book is structured so that the first three chapters provide an introduction and prepare the reader for chapters 4 to 6, which expand the formulations to electromagnetic and optical str.